When all computers shut down: the clinical impact of a major cyber-attack on a general hospital - Abbou, Benyamine; Kessel, Boris; Ben Natan, Merav; Gabbay-Benziv, Rinat; Dahan Shriki, Dikla; Ophir, Anna; Goldschmid, Nimrod; Klein, Adi; Roguin, Ariel; Dudkiewicz, Mickey (Frontiers in Digital Health, 2024)
Importance: Healthcare organizations operate in a data-rich environment and depend on digital computerized systems, thus may be exposed to cyber threats. Indeed, healthcare systems are among the most vulnerable sectors to hacks and malware. However, the impact of cyber-attacks on healthcare organizations remains under-investigated.Objective: To describe a major attack on an entire medical center which resulted in complete shut-down of all computer systems, and to identify the most essential interventions required in order to return to normal activity.Setting: A public, general and acute care, referral university teaching hospital.Methods: Report the different recovery measures on various hospital clinical activities, and their impact on clinical work.The malfunctioning of hospital computer systems did not reduce the number of heart catheterizations, births, or outpatient clinic visits. However, a sharp drop in surgical activities, emergency room visits, and total hospital occupancy was observed immediately and during the first post-attack week. A gradual increase in all clinical activities was detected starting in the second week after the attack, with a significant increase of 30% associated with the restoration of electronic medical records and laboratories module, and a 50% increase associated with the return of the imaging module archiving. One limitation of the present study is that due to the retrospective design of this study, there were no data regarding the number of elective internal care hospitalizations that were considered crucial.The risk of ransomware cyberattacks is growing.Healthcare systems at all levels should recognize this threat and have protocols for implementation once this catastrophic event occurs. Careful evaluation of steady computer system recovery on a weekly basis enables vital hospital function, even under a major cyber-attack. The restoration of electronic medical records, laboratory systems, and 4 imaging archiving modules were found to be the most significant factors, allowing the return to normal clinical hospital work.